Serum Uric Acid Level in Oral Cancer Patients -Original Study - G. Florence Sangeetha; K.M.K. Mastan; N. Aravindha Babu; S. Leena Sankari; Jayasri Krupa; T. Gopala Krishnan (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background Uric acid is a result of the metabolic breakdown of purine digestion. Serum uricacid ensures against carcinogenesis by means of its cell reinforcement properties and forestalls thedevelopment of oxygen extremists. High blood groupings of uric acid can prompt gout and are relatedwith diabetes and development of kidney stones. Serum uric acid fixation mirror the harmony betweenuric acid combination and discharge. Studies have indicated that high uric acid is a danger factorfor hypertension, diabetes and Cardio Vascular illness.Squamous cell carcinoma is characterized asthreatening epithelial neoplasm showing squamous separation as described by the development of keratinor the bury cell spans. It also includestheinitialpresenceofaprecancerous lesion.Moreover,specificmedicalconditionscancontributetotheoral potentially malignant disordersprevalenceOral squamous cellcarcinoma is the most well-known neoplasm speaking to over 80% of all oral malignancy cases. Serum uricacid has been proposed to be related with the danger of malignant growth and it was seen that raised degreesof serum uric acid was related with an expanded disease frequency contrasted with typical qualities.Aim and Objectives : The aim of this study is to evaluate the serum uric acid level in oral cancer patients,to find out the association between low serum uric acid level and risk of squamous cell carcinoma and tocompare the serum uric acid levels in oral cancer patients with normal individuals.Materials and Methods : This is a hospital based study to find out the uric acid level in oral cancer patients.The participants were selected from the out patients, Department of Oral Pathology and Microbiology. Thestudy included a total numbe of 28 persons. Out of the 28 persons 15 oral cancer patients were selected forthe experimental group. The remaining 13 subjects were in the normal group.Results : In this study, mean uric acid level in this stroke population with CAD is 6.37 mgs/dl and in thosewithout CAD is 5.00 mgs/dl and thus establishes a statistically significant relationship (‘p’0.0004). Whenmales and females are considered, males have a significant association with a ‘p’ value of 0.0003. The buccalmucosa of the oral cavity was the most common involved site followed by the vestibule.Conclusion : The studies showed that serum uric acid level was significantly lower in oral cancer patientscompared to the control group. Uric acid may prevent the formation of oxygen radicals and there by protectagainst carcinogenesis. In human’s uric acid is the most abundant antioxidant and is an important intracellular free radical scavenger. Early detection of oral cancer and Habit should be controlled to reducemortality rates and help to provide successful cancer treatment.